ECF and TCF bleaching of Saccharum officinerum-CO89003 bagasse soda-AQ pulp with alkali-thermo-tolerant crude xylanase from Coprinellus disseminatus SW-1 NTCC1165 - Swarnima Agnihotri; Dharm Dutt; A. K. Vidyarthi (BioResources, 2012)
An alkali-thermo-tolerant crude xylanase from Coprinellus disseminatus SW-1 NTCC1165 produced under solid-state fermentation conditions improves the brightness of sugarcane bagasse soda-AQ pulp by 7.3, 4.7, 6.1, and 8.2% in XODED, XOD(EOP)DP, OX(EOP)P, and XO(EOP)P bleaching sequences, respectively, at an enzyme dose of 8IU/g, a reaction time of 120 min, a consistency of 10%, and a pH of 6.4 at 55 oC. An improvement in brightness by 2.1% for pulp bleached by XO(EOP)P compared to OX(EOP)P sequence validates that xylanase treatment is more effective for hydrolysing lignin-carbohydrates complexes before oxygen treatment. AOX after XODED and XOD(EOP)DP sequences is reduced by 41.43 and 40%, respectively, compared to controls, but an increase in COD and color in studied bleaching sequences is attributable to the hydrolysis of hemicelluloses and the release of lignin-carbohydrates complexes after xylanase treatment. Xylanase treatment modifies fibre surface by introducing cracks, peelings, swelling, and external fibrillation, which facilitates faster penetration of bleach chemicals by disrupting physical barriers, as revealed by scanning electron microscopy.